Justification for a regulatory proposal for sound broadcasting and transmobile services in Colombian borders (2015)
Nowadays, in Colombia there are neither rules nor agreements that regulate transmobile and broadcasting sound services in its borders. This paper aims to justify the need to regulate these services through a study in three border areas: Ipiales-Tulcán (Ecuador); Puerto CarreñoPuerto Ayacucho (Venezuela) and Leticia-Tabatinga (Brazil)-Santa Rosa (Peru), to identify possible scenarios of interference from neighboring countries to Colombia. In this context, we performed simulations with the software Radio Mobile to assess the magnitude of the interference. The results show cases of interference between mobile and fixed services, which require control because they could potentially affect communications to the safety and emergency care of people. This also hinders the process for allocating spectrum and screening of new channels for radio broadcasting services and transmobile.